Reelin Signaling Controls the Preference for Social Novelty in Zebrafish - Dalla Vecchia, Elisa (Front Behav Neurosci, 2019)
Reelin (Reln) is an extracellular glycoprotein that is important for brain patterning. During development Reln coordinates the radial migration of postmitotic cortical neurons, cerebellar and hippocampal neurons, whereas it promotes dendrite maturation, synaptogenesis, synaptic transmission, plasticity and neurotransmitter release in the postnatal and adult brain. Genetic studies of human patients have demonstrated association between the RELN locus and autism spectrum disorder, schizophrenia, bipolar disorder, and Alzheimer’s disease. In this study we have characterized the behavioral phenotype of reelin (reln) mutant zebrafish, as well as two canonical signaling pathway targets DAB adaptor protein 1a (dab1a) and the very low density lipoprotein receptor (vldlr). Zebrafish reln(–/–) mutants display a selective reduction in preference for social novelty that is not observed in dab1a(–/–) or vldlr(–/–) mutant lines. They also exhibit an increase in 5-HT signaling in the hindbrain that parallels but does not underpin the alteration in social preference. These results suggest that zebrafish reln(–/–) mutants can be used to model some aspects of human diseases in which changes to Reln signaling alter social behavior.